2022
DOI: 10.1108/qae-01-2022-0016
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between social media based teaching and academic performance during COVID-19

Abstract: Purpose The closure of educational institutions in the COVID-19 pandemic has changed the global teaching and learning landscape. Face-to-face classroom activity has been shifted to online classroom activity. This study aims to investigate the effect of social media-based education on students’ academic performance during the pandemic. Design/methodology/approach This study analyzes the perceptions of 302 university-going students of Bangladesh using structural equation modeling. Findings Results show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…During online lectures, a variety of learning tools are used, including Microsoft Teams, Zoom, Google Meet, WhatsApp Group Media, and others (28,29). The existence of an internet network to support diverse learning platforms is the primary prerequisite for online learning (30,31).…”
Section: Resultsmentioning
confidence: 99%
“…During online lectures, a variety of learning tools are used, including Microsoft Teams, Zoom, Google Meet, WhatsApp Group Media, and others (28,29). The existence of an internet network to support diverse learning platforms is the primary prerequisite for online learning (30,31).…”
Section: Resultsmentioning
confidence: 99%
“…Social media engagement in this study points to the closeness of relationships and values that support using social media, although it is not fully utilized for learning purposes. This is as stated by Ghosh [31], that not all students consider social media useful for communication and learning. The results of this study indicate that social media has great potential to support learning.…”
Section: Structural Modelmentioning
confidence: 88%
“…Ghosh et al. (2023) did a study with 302 undergraduates in Bangladesh to ascertain the effectiveness of social media-based training on academic performance during the outbreak of the coronavirus disease 2019 (COVID-19).…”
Section: Social Media and Contemporary Societymentioning
confidence: 99%
“…Ghosh et al (2023) did a study with 302 undergraduates in Bangladesh to ascertain the effectiveness of social media-based training on academic performance during the outbreak of the coronavirus disease 2019 (COVID-19). The researcher used a survey research design and found that training during COVID-19 significantly contributed in enhancing the academic performance of learners during the outbreak of COVID-19.…”
mentioning
confidence: 99%